I'jaz Al-Qur'an - Irma Sani Daulay (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2022)
Every Prophet of Allah swt., gave miracles according to the conditions and conditions of the people faced at that time. Miracles are instructions from Allah swt., to humans for the truth of His Apostles and Prophets. They are truly the messengers of Allah and they are only giving news, conveying messages from Allah swt. Allah gave miracles to prove the truth of his prophethood and apostleship. It is usually not easy for every people to accept the call / da'wah of the Apostles before they know the proof of the truth that he is the messenger of Allah. So a miracle was needed so that his people could accept his call. The miracles that the Prophet Muhammad received were numerous, but the biggest one is the Al-Qur'an Al-Karim, the last divinely revealed holy book that was revealed to his Prophet as a guide and guide for all mankind in the world, a holy book that will be kept pure. by Allah until the end of time, the contents of the Qur'an Al-Karim include, for unseen news (The occurrence of war between the Roman Empire and the Persian Empire and the victory on the Roman side), historical information (the story of the Prophet Adam, the prophet Noah and others are events thousands of years before the Prophet Muhammad, peace be upon him), science (the Qur'an hints that